Growth and endocrine function in children with Dravet syndrome. (November 2017) - Eschbach, Krista; Scarbro, Sharon; Juarez-Colunga, Elizabeth; Allen, Victoria; Hsu, Stephanie; Knupp, Kelly
Highlights: Abnormal IGF-1 and testosterone levels may be seen in children with Dravet syndrome. Children with Dravet syndrome can have associated short stature and growth delay. Consider further endocrine evaluation in children with Dravet syndrome that have reduced growth percentiles. Abstract: Purpose: Dravet syndrome is an intractable childhood epilepsy syndrome most often associated with an SCN1A mutation. In our clinical practice, several patients with Dravet syndrome were noted to have short stature and endocrine dysfunction. This has not been reported in the literature. Our study aim was to describe growth measurements and endocrine abnormalities in children with Dravet syndrome. Method: A retrospective chart review was performed at a single institution. Eligibility criteria included clinical and genetic ( SCN1A ) diagnosis of Dravet syndrome. Records were reviewed for height and weight measurements and serologic evidence of endocrine abnormality, as well as patient demographics, anti-seizure medication, and family history. Age and gender specific trend of height and weight measurements, using z-scores, were compared to CDC growth curves (Centers for Disease Control and Prevention [1]). Results: Sixty-eight children were identified, 46% male, age 1–21 years, taking an average of 2.9 anti-seizure medications per patient. Mean growth parameter measurements were significant for decrease in height z-score of 0.10 (p = < 0.001) and decrease in weight z-score of 0.09 (p = < 0.01) for every year increase in age, such that with increasing age the cohort moved farther away from the mean. The average group height and weight z-score, at age 8, was −0.45 and −0.09, respectively. After adjusting for age, neither gender, family history, or anti-seizure medication was associated with height or weight z-score. Serologic endocrine results were available for 26 children (38%). This identified low insulin-like growth factor 1 (IGF-1) in 7/15 and low testosterone in 2/10. Two children received growth hormone supplementation. TSH testing was abnormal <10% of the time. Conclusions: Comorbidities in children with Dravet syndrome may involve more systems than previously reported. We report a cohort of children with Dravet syndrome with reduced height and weight growth trend, as well as a subset with endocrine dysfunction evidenced by low IGF-1 and testosterone levels. Additional prospective research is needed to further define the significance of this relationship.